PROSES PEMBUMIAN KONSEP TAJDID MUHAMMADIYAH SEBAGAI GERAKAN ISLAM MODERNIS - HIMAWAN SUTANTO (Jurnal Dialog, 2017)
The article explores the development of Muhammadiyah in historical perspective and focuses more on Tajdid as modern Islamic movement. Tajdid movement of Muhammadiyah is always aimed to solve the problems faced by ummah based on Al-Qur’an and Sunnah. While the circumstance of Ummah is always changed, the Tajdid should be conducted in line with the changes. Due to Tajdid, Muhammadiyah’s image as a puritanical and inflexible Islamic movement slowly began to erode. Nowadays, Tajdid continuous and is initiated by Muhammadiyah Young Intelectual Network (JIMM/Jaringan Islam Muda Muhammadiyah) to promote Islam Rahmatan Lil Alamin, to bridge the dispute of religious thoughts, to solve religious, social, cultural and economic problems such as poverty, human rights, democracy, religions harmony and the like. Finally, the article concludes the tajdid movement of Muhammadiyah has made Islam Indonesia as moderate Islam.